Coercion, Consent, and Class Consciousness: How Workers Respond to Amazon’s Production Regime - Vallas Steven P.; Kronberg Anne-Kathrin (Sage, 2025)
Although the “logistics revolution” has powerfully transformed contemporary capitalism, little is known about how logistics workers view such changes. To address this gap, the authors explore how Amazon’s labor practices shape workers’ orientations toward their jobs and class positions. Using a mixture of in-depth interviews and survey data, the authors find that Amazon’s production regime has contradictory effects on workers’ orientations. Digital surveillance augments managerial coercion, fostering an alienated relation toward work and a heightened sense of exploitation. Yet the company’s ability to hire precariously situated workers supplies it with workers who clearly consent to such labor practices. These results underscore the duality of managerial regimes among warehouse workers and begin to explain the ordeal of union formation, as workers adopt sharply distinct views of the working conditions they confront.